Develop practical methods of knowledge measurement in universities - Al-Oqaily A.T.; Hassan Z.B.; Al DalaIen A.A.-H.; Rashid A.M. (Asian Research Publishing Network, 2023)
The organizations of various fields such as industry and education looking for manage their knowledge resources in order to provide efficient products performance. The knowledge measurement is one from the most important success factors of knowledge management implementations. The dynamic changes of businesses environments and knowledge levels maximize the difficulty of measure the efficiency levels of tacit and explicit knowledge. The academic staff in universities face challenges in retrieve the efficient explicit knowledge i.e. articles that compatible with their tacit levels in order to develop their tacit value to support their teaching and researching activities. The main aim of this research is to develop practical methods to match between the explicit and tacit knowledge levels inside universities environments in order to retrieve the suitable explicit knowledge that satisfy the employees needs of knowledge based on their tacit levels. This research data collected supporting qualitative data collecting method using interview with four experts of knowledge management. The knowledge measurement practical specifications and mathematic equations developed based on the collected data to provide the matching between the tacit levels of academic staff and retrieved explicit knowledge levels inside universities environments. 2005 - 2015 JATIT & LLS. All rights reserved.